Memorable tourism experience of hikers at Gunung Baling, Kedah - Ayob, Norfarah Diana (2018)
In the highly competitive tourism marketplace, the importance of achieving success is by providing visitors with Memorable Tourism Experiences (MTE). Gunung Baling became one of the attractions to hike after becoming viral in social media in 2015. Several hikers re-hiked Gunung Baling more than once. Thus, this study is to examine the eight dimensions of MTE scale items and factors influencing hikers’ MTE during hiking at Gunung Baling. A total of 162 hikers who had completed hiking at Gunung Baling were purposively sampled for the study. The data was analyzed using descriptive and multiple regression analysis. Hedonism has shown the highest mean value among all MTE scale items. Hikers’ accompaniment, sources of information (WOM), recommendation to other hikers, and hikers’ re-hike interest are significant factors that influence hikers’ MTE at Gunung Baling, Kedah. The management of Gunung Baling should continuously provide a variety of activities to ensure greater memorable experiences among the hikers.